PENGARUH TINGKAT KETEPATAN WAKTU PENYEDIAAN REKAM MEDIS RAWAT JALAN TERHADAP EFEKTIVITAS PELAYANAN REKAM MEDIS DI RUMAH SAKIT UMUM DAERAH MAJALAYA - Kamelia Nurhasanah (INFOKES (Informasi Kesehatan), 2022)
This research aims to know the effect of the timeliness of providing outpatient medical records on the effectiveness of medical record services at the Majalaya Regional General Hospital.The research method used is a quantitative method with a descriptive approach. The data collection technique used is observation, questionnaires, and literature study. The sample collection technique used a simple random sampling technique with the sample object in this research being outpatient medical record documents totaling 100 documents and 15 medical record officers. Based on the result of the research, the effect of the timeliness of providing outpatient medical records on the effectiveness of medical record services at the Majalaya Regional General Hospital was 84,2%. In the provision of outpatient medical records, there are 28 documents (28%) on time and 72 documents (72%) not on time, and the average time for providing medical records as a whole is about 20,15 minutes.From the research conducted, there are several problems : (1) there is still an inaccuracy in the time of providing outpatient medical records, (2) the timing of providing outpatient medical records is not in accordance with SPM, (3) and not optimal supervision of medical record documents. The suggestions given to the hospital : (1) coordinating with medical record officers to be more careful, thorough, fast and precise in storing or providing medical records, (2) conducting socialization with medical record officers about the importance of SPM when providing outpatient medical records on the effectiveness of service, (3) conducting routine evaluations related to the supervision of medical record documents.